2013
DOI: 10.1021/jp404714c
|View full text |Cite
|
Sign up to set email alerts
|

Folding Dynamics of the Trp-Cage Miniprotein: Evidence for a Native-Like Intermediate from Combined Time-Resolved Vibrational Spectroscopy and Molecular Dynamics Simulations

Abstract: Trp-cage is a synthetic 20-residue miniprotein which folds rapidly and spontaneously to a well-defined globular structure more typical of larger proteins. Due to its small size and fast folding, it is an ideal model system for experimental and theoretical investigations of protein folding mechanisms. However, Trp-cage's exact folding mechanism is still a matter of debate. Here we investigate Trp-cage's relaxation dynamics in the amide I' spectral region (1530-1700 cm(-1)) using time-resolved infrared spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
90
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(120 citation statements)
references
References 80 publications
(204 reference statements)
22
90
1
1
Order By: Relevance
“…In addition, these findings corroborate with the recent IR experiment of Meuzelaar et al 19 Interestingly enough, we found that the intermediate I state, consisting of a formed α-helix with a solvated and 24,28 We can solve this paradox, by constructing the free energy landscape.…”
Section: The Stationary Distribution or Equilibrium Populationsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, these findings corroborate with the recent IR experiment of Meuzelaar et al 19 Interestingly enough, we found that the intermediate I state, consisting of a formed α-helix with a solvated and 24,28 We can solve this paradox, by constructing the free energy landscape.…”
Section: The Stationary Distribution or Equilibrium Populationsupporting
confidence: 92%
“…All other timescales are fast processes related to transitions between the metastable states. Recent IR experiments by Meuzelaar et al 19 found biexponential kinetics for the Trp cage system. At a temperature of 300 K, they measured a slow time scale of 2200 ns, and a fast timescale of around 150 ns, which they attribute to the presence of an intermediate.…”
Section: Timescalesmentioning
confidence: 98%
See 3 more Smart Citations